ANALYSIS OF SOFTWARE ADAPTED TO THE EDUCATIONAL PROCESS AND ITS CAPABILITIES (World Bulletin of Education and Learning, 2025)
In this article, pedagogical software applications can be considered entertainment or social networking applications, but mobile applications have so far proved to be an educational tool. Over time, the development of a variety of programs has made the preparation of a new generation of e-learning resources more meaningful and user-friendly. All of this allows for the rapid exchange and assimilation of information electronically. It is important that the information provided is relevant to the user. With so much information in the world, choosing the right one is becoming a challenge. In order to avoid such situations, many of our teachers create and use e-learning resources in their subjects, which are as basic as possible and important for students to master. enriched with. Of course, the role of programs that create e-learning resources is important in this process. Over time, the capabilities of such programs have expanded and are being put into practice. Inexpensive, easy-to-use, and high-quality mobile learning resources are taking a variety of forms in the market. In this chapter, we have created a mobile learning resource based on Java technologies and analyzed the different methods of using them to create an optimal teaching methodology.
Keywords: Programming languages, mobile applications, web applications, pedagogical software, software, Hybrid applications.